Manufacturing Tibetan medicine : the creation of an industry and the moral economy of Tibetanness - Saxer, Martin, 1971- (Epistemologies of healing, 2013)
Within a mere decade, hospital pharmacies throughout the Tibetan areas of the People's Republic of China have been converted into pharmaceutical companies. Confronted with the logic of capital and profit, these companies now produce commodities for a nationwide market. While these developments are depicted as a big success in China, they have also been met with harsh criticism in Tibet. At stake is a fundamental (re- )manufacturing of Tibetan medicine as a system of knowledge and practice. Being important both to the agenda of the Party State's policies on Tibet and to Tibetan self-understan.